Pendampingan dan Pelatihan Penentuan Harga Pokok Produksi Pastel Mini UMKM Rizki Kanaya - Nasihin, Ihsan; Lasmini, Lilis; Imroatul Fatihah, Dhea; Purwandari, Dian (Universitas Muhammadiyah Malang, 2024)
Purpose – This community service activity aims to carry out training in calculating the cost of production of dry mini pastel products carried out by UMKM Rizki Kanaya. Design/methodology/approach – The method used in this service is by means of training and summaries regarding calculating the cost of production. The training was carried out by delivering material on calculating the cost of production to MSME Rizki Kanaya employees. The next step is to carry out a direct calculation simulation of the cost of production of Rizki Kanaya UMKM mini pastel products. Findings – The community service activities carried out obtained the result that Rizky Kanaya MSMEs still did not differentiate between raw materials and auxiliary materials. This service can help MSME Rizky Kanaya first separate raw materials and auxiliary materials in calculating mini pastel production costs. So you can determine a selling price that is able to compete with competitors in the market. Originality/value – Through this community service program activity, we can overcome the problem of determining the cost of production in terms of differentiating between raw materials and auxiliary materials as components that form the cost of production for MSME Rizky Kanaya.